The Effectiveness of Various Instructional Models on Motivation and Science Learning Outcomes Among Elementary School Students - Zakila Noor Khaira; Rohmani (Universitas Pendidikan Ganesha, 2026)
Science learning in elementary schools still faces several challenges, particularly the low level of student participation during the learning process. This condition affects students’ learning motivation and academic achievement in science. One contributing factor is the use of monotonous learning strategies that do not fully encourage students’ active involvement in understanding science concepts. This study aims to examine, analyze, and synthesize the effectiveness of various learning approaches in improving students’ motivation and science learning outcomes at the elementary school level. This research employed a systematic literature review method by analyzing 10 relevant scientific articles published between 2021 and 2025. Data were collected through documentation using a data identification sheet containing information on learning models, implementation characteristics, and research findings. The data were analyzed thematically through data reduction, theme classification, comparison of findings, and systematic synthesis. The findings indicate that problem-based learning, guided inquiry, discovery learning, cooperative learning, and technology-based learning significantly contribute to improving students’ motivation and science achievement. Learning that emphasizes active participation, interaction, and independent exploration is proven to be more effective in creating meaningful learning experiences. These findings highlight the importance of selecting innovative, flexible, and student-oriented learning models.